2012
DOI: 10.1088/0957-4484/23/31/315102
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Fe3O4@Au superparamagnetic nanoparticles:in vitrobioactivity

Abstract: The interaction of nanoparticles with cells has been a focus of interest during the past decade. We report the fabrication and characterization of hydrosoluble Fe₃O₄@Au nanoparticles functionalized with biocompatible and fluorescent molecules and their interaction with cell cultures by visualizing them with confocal microscopy. Gold covered iron oxide nanoparticles were synthesized by reducing metal salts in the presence of oleylamine and oleic acid. The functionalization of these particles with an amphiphilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…The tendency of NMs (Bhattacharjee et al 2013;Fröhlich et al 2012;Sohaebuddin et al 2010). 3T3 cell model is considered very sensitive to verify in vitro cytotoxic effects of NMs (Uboldi et al 2012;Mahto et al 2010), while HeLa tumor cell line is a culture model widely used in cytotoxicity and especially in cell uptake studies of a broad range of particulate nanocarriers (Kelsch et al 2012;Salado et al 2012). The tumor HeLa cell line was more resistant to NV cytotoxic effects, which was in agreement with our previous study (Nogueira et al 2011b).…”
Section: Discussionsupporting
confidence: 87%
“…The tendency of NMs (Bhattacharjee et al 2013;Fröhlich et al 2012;Sohaebuddin et al 2010). 3T3 cell model is considered very sensitive to verify in vitro cytotoxic effects of NMs (Uboldi et al 2012;Mahto et al 2010), while HeLa tumor cell line is a culture model widely used in cytotoxicity and especially in cell uptake studies of a broad range of particulate nanocarriers (Kelsch et al 2012;Salado et al 2012). The tumor HeLa cell line was more resistant to NV cytotoxic effects, which was in agreement with our previous study (Nogueira et al 2011b).…”
Section: Discussionsupporting
confidence: 87%
“…It is a challenge however, to directly obtain monodispersed NPs in aqueous media due to the complexity of controlling the nucleation and growth processes at room temperature, giving rise to particles with low crystallinity, low saturation magnetization, and broad size distribution. Salado et al 144 145 The results showed that cell viability remained above 92% when using Fe 3 O 4 -Au NPs at a concentration as high as 2.0 mg/mL, suggestive of the biocompatibility of the nanoparticles. The IC 50 (0.731 g/mL) of the Dox-Fe 3 O 4 -Au group was higher than that (0.522 g/mL) of the Dox group (P < 0 05).…”
Section: Cytotoxicity Of Magnetic-plasmonic Nanomaterials In Vitro Anmentioning
confidence: 97%
“…It is well known that catechols are excellent ligands for Fe 3 O 4 surfaces and conjugation to PEG yields in highly stable probes while maintaining the magnetic properties. 29,30 Synthesis and phase transfer of Fe 3 O 4 -Au core-shell NPs Gold shells around the IONP core can be formed using two approaches: directly on the IONP surface [31][32][33][34][35][36][37] or onto a middle layer, consisting of silica or a polymer which serves as a bridge between the IONP core and the gold shell. 21,[38][39][40][41][42][43][44] We synthesised NPs with the gold shell directly on the IONP core according to a reported procedure.…”
Section: Synthesis Of Bifunctional Coating Ligandsmentioning
confidence: 99%